1974
DOI: 10.1172/jci107584
|View full text |Cite
|
Sign up to set email alerts
|

Ketone-body production and oxidation in fasting obese humans.

Abstract: A B S T R A C T Rates of plasma acetoacetate and total ketone-body production and oxidation to C02 were determined by an isotope tracer technique in eight obese subjects undergoing progressive starvation. After a brief fast and under conditions of mild ketonemia and minimal ketonuria, rates of acetoacetate and total ketone-body production and oxidation were directly related to the increasing plasma concentration. After a longer fast and with severer ketonemia, acetoacetate and total ketone-body production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

1974
1974
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(81 citation statements)
references
References 25 publications
4
75
0
2
Order By: Relevance
“…Plasma ketone body concentrations were similar throughout the fast ( Fig. 1C ), suggesting that men and women have similar rates of ketogenesis ( 37 ). Similarly, there were no differences in the rates of hepatic oxidative metabolism at the level of the TCA cycle ( Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Plasma ketone body concentrations were similar throughout the fast ( Fig. 1C ), suggesting that men and women have similar rates of ketogenesis ( 37 ). Similarly, there were no differences in the rates of hepatic oxidative metabolism at the level of the TCA cycle ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Some individuals (women = 6, men = 5) were re-fed a low-fat meal (60% carbohydrate, 25% fat, and 15% protein; women = 567 and men = 667 kcal), and insulin and glucose excursion were assessed. In the 4 h after refeeding, peak insulin was signifi cantly higher in women (46 [37][38][39][40][41][42][43][44][45][46][47] vs. 20 [15][16][17][18][19][20][21][22][23][24][25] U/ml; P = 0.011), whereas peak glucose concentration did not differ between sexes ( P = 0.233). These fi ndings indicated reduced insulin sensitivity in women after short-term fasting.…”
Section: Insulin and Glucose Excursion After Refeedingmentioning
confidence: 99%
“…Support for this proposal can be obtained from the observations that the maximum rates of total ketone-body utilization (oxidation) and production were achieved at blood concentration of about 2-3 mmol/liter (32,33), a value found in both lean and obese subjects after about 3 days of starvation (1,2,5).…”
Section: Resultsmentioning
confidence: 94%
“…With regard to the latter, there is a special difficulty in relation to ketone bodies since we infused only [14C]hydroxybutyrate, whereas both hydroxybutyrate and acetoacetate might contribute to oxidation. When we began this work, we assumed that these two ketone bodies were essentially in isotopic equilibrium as had been reported by Bergman et al (1963) Guest & Foster, 1970) in rats, it has been shown that the method used by Bergman et al (1963) for measurement of specific activities of ketones is not well suited for demonstrating an absence of isotopic equilibrium, and absence of such an equilibrium has been shown both in rats (McGarry et al 1970;Bates, 1971) and in man (Reichard, Owen, Haff, Paul & Bortz, 1974). If this were true in the sheep, the specific activity of acetoacetate would be lower than our measured specific activity of 3-hydroxybutyrate, and since the average specific activity of 'total' ketones would be less, the actual fraction of CO2 derived from both ketones would be greater than our estimate.…”
mentioning
confidence: 91%